Australia's mining productivity paradox: implications for MFP measurement - Zheng, S.; Bloch, Harry (Centre for Research in Applied Economics, Curtin Business School, 2010)
This paper investigates the mining industry's poor productivity performance as measured by the conventional multifactor productivity (MFP) index during the recent mining boom in Australia. We derive a relationship between the measured and 'true' MFP growth that separates the effects of returns to scale, market power, capacity utilisation and natural resource inputs from measured MFP. Using exploration capital as a proxy for natural resource inputs, a translog variable cost function is estimated to provide parameter estimates for the various components in the decomposition equation. The results show that the average MFP growth in Australian mining based on the dual measure of technical change is nearly 2% over the sample period 1974-75 to 2006-07, rather than 0.01% from the published index. The difference arises because changes in natural resource inputs have subtracted 1.14 percentage points from the 'true' MFP growth, while the effects of capacity utilisation and returns to scale are also negative but less sizeable in impact.